Organizational Communication: Communication and Motivation in The Workplace - Sari Ramadanty; Handy Martinus (Bina Nusantara University, 2016)
Every human activity was basically driven by the motivation. Work motivation was a condition or an energy that directed employees to achieve organizational goals of the company. Nowadays, the development of organizational communication saw the communication as one of the most dominant and important activity in the organization and it could be able to motivate employees. The purpose of this study was to reveal how the role of the communication that occurs within the organization could give the motivation to employee. The problem of the research was the relationship employee motivation with factors of communication, such as nonverbal communication, interpersonal communication leadership and communication climate. The method used descriptive qualitative method. Methods of data collection of this study were literature study. Research finds that nonverbal communication, interpersonal communication leadership and communication climate have a significant role to form employee motivation. Nonverbal communication has slightly strong role in shaping the positive motivation to employee. The role includes body communication, facial communication and eye communication. Interpersonal communication leader is based on the satisfaction level of information between management and employees. Management and transparency in openness in downward communication under the form of information from superiors are by listening the communication between supervisors and employees are running smoothly.